Auctions as Coordination Devices - Maarten C.W. Janssen (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper develops an economic argument relating auctions to high market prices. At the core of the argument is the claim that market competition and bidding in an auction should be analyzed as part of one game, where the pricing strategies in the market subgame depend on the bidding strategies during the auction. I show that when there are two licenses for sale the only equilibrium in the overall game that is consistent with the logic of forward induction is the one where firms bid an amount (almost) equal to the profits of the cooperative market outcome and follow a cooperative pricing strategy in the market game resulting in high prices. With three or more licenses the auction format determines whether the forward induction argument works.
Keywords: L50; 330; Auctions; Market prices; Coordination; Auktionstheorie; Preismanagement; Spieltheorie; Koordination